A census of star-forming galaxies in the z~9-10 universe based on HST+spitzer observations over 19 CLASH clusters: three candidate z~9-10 galaxies and improved constraints on the star formation rate density at z~9 - Bouwens, Rychard J.; Zitrin, Adi; Carrasco, Mauricio; Bartelmann, Matthias (Arxiv, 2014)
We utilise a two-color Lyman-Break selection criterion to search for z~9-10 galaxies over the first 19 clusters in the CLASH program. A systematic search yields three z~9-10 candidates. While we have already reported the most robust of these candidates, MACS1149-JD, two additional z~9 candidates are also found and have H_{160}-band magnitudes of ~26.2-26.9. A careful assessment of various sources of contamination suggests <~1 contaminants for our z~9-10 selection. To determine the implications of these search results for the LF and SFR density at z~9, we introduce a new differential approach to deriving these quantities in lensing fields. Our procedure is to derive the evolution by comparing the number of z~9-10 galaxy candidates found in CLASH with the number of galaxies in a slightly lower redshift sample (after correcting for the differences in selection volumes), here taken to be z~8. This procedure takes advantage of the fact that the relative volumes available for the z~8 and z~9-10 selections behind lensing clusters are not greatly dependent on the details of the lensing models. We find that the normalization of the UV LF at z~9 is just 0.28_{-0.20}^{+0.39}× that at z~8, ~1.4_{-0.8}^{+3.0}x lower than extrapolating z~4-8 LF results. While consistent with the evolution in the UV LF seen at z~4-8, these results marginally favor a more rapid evolution at z>8. Compared to similar evolutionary findings from the HUDF, our result is less insensitive to large-scale structure uncertainties, given our many independent sightlines on the high-redshift universe.